2017
DOI: 10.1128/aac.02498-16
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacodynamic Evaluation of Fosfomycin against Escherichia coli and Klebsiella spp. from Urinary Tract Infections and the Influence of pH on Fosfomycin Activities

Abstract: Fosfomycin is widely used for the treatment of uncomplicated urinary tract infection (UTI), and it has recently been recommended that fosfomycin be used to treat infections caused by multidrug-resistant (MDR) Gram-negative bacilli. Whether urine acidification can improve bacterial susceptibility to fosfomycin oral dosing regimens has not been analyzed. The MIC of fosfomycin for 245 Gramnegative bacterial isolates, consisting of 158 Escherichia coli isolates and 87 Klebsiella isolates which were collected from … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
31
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(35 citation statements)
references
References 44 publications
4
31
0
Order By: Relevance
“…Our results confirm that low pH values increase FOS activity (41,43). In an acidic urine (pH values of 5 to 6), FOS is partially protonated and in a more lipophilic state, allowing FOS to enter bacteria and resulting in higher antimicrobial activity (43). As we previously demonstrated, the urine pH for patients with UTI caused by E. coli is mainly acidic (85.38% of patients have a urine pH of Յ6.5) (35).…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…Our results confirm that low pH values increase FOS activity (41,43). In an acidic urine (pH values of 5 to 6), FOS is partially protonated and in a more lipophilic state, allowing FOS to enter bacteria and resulting in higher antimicrobial activity (43). As we previously demonstrated, the urine pH for patients with UTI caused by E. coli is mainly acidic (85.38% of patients have a urine pH of Յ6.5) (35).…”
Section: Discussionsupporting
confidence: 86%
“…Our results confirm that low pH values increase FOS activity (41,43). In an acidic urine (pH values of 5 to 6), FOS is partially protonated and in a more lipophilic state, allowing FOS to enter bacteria and resulting in higher antimicrobial activity (43).…”
Section: Discussionsupporting
confidence: 80%
“…Fosfomycin activity observed in infected kidneys may result from the combination of local specific physiological conditions in urine and of fosfomycin concentrations in the kidneys. Indeed, several authors have already shown that low pH values increased fosfomycin in vitro activity (12, 19, 20). In an acidic environment such as urine, fosfomycin is partially protonated, being in a more lipophilic state, allowing fosfomycin entry into bacteria, and resulting in higher antimicrobial activity (20).…”
Section: Discussionmentioning
confidence: 98%
“…Indeed, several authors have already shown that low pH values increased fosfomycin in vitro activity (12, 19, 20). In an acidic environment such as urine, fosfomycin is partially protonated, being in a more lipophilic state, allowing fosfomycin entry into bacteria, and resulting in higher antimicrobial activity (20). Our results support these findings, as low pH values were associated with a significant decrease in fosfomycin MIC values for resistant strains into the susceptible range (Table 1).…”
Section: Discussionmentioning
confidence: 98%
“…Indeed, several authors have already shown that low pH values increased the fosfomycin in vitro activity (12,18,19). In an acidic environment, such as urine, fosfomycin is partially protonated, thus being in a more lipophilic state, allowing fosfomycin entry into bacteria and resulting in higher antimicrobial activity (19).…”
Section: Discussionmentioning
confidence: 99%